Generous Pragmatism - James Pfeiffer (Oz, 2014)
In their introduction to the book, Nurture, about BNIM's work, authors Rodolphe el-Khoury and Andrew Payne spoke about the emergence of a new pragmatism in contemporary architecture, a concern with "how well buildings perform in response to the full range of social and ecological issues they are called on to organize."